Negotiator Behavior Under Arbitration - Bloom, David E.; Cavanagh, Christopher L. (American Economic Review, 1987)
The emerging empirical literature on the economics of arbitration has focused primarily on the behavior of arbitrators under alternative forms of arbitration. This article suggests that it is natural for empirical economists to now expand their focus to include issues related to the behavior of negotiators. In this connection, three key aspects of negotiator behavior are discussed: (1) the decision to settle a dispute voluntarily or to proceed to arbitration; (2) the strategy for selecting an arbitrator; and (3) the final bargaining position to advance before an arbitrator.